2014
DOI: 10.1371/journal.pone.0114207
|View full text |Cite|
|
Sign up to set email alerts
|

Emotion Attribution to a Non-Humanoid Robot in Different Social Situations

Abstract: In the last few years there was an increasing interest in building companion robots that interact in a socially acceptable way with humans. In order to interact in a meaningful way a robot has to convey intentionality and emotions of some sort in order to increase believability. We suggest that human-robot interaction should be considered as a specific form of inter-specific interaction and that human–animal interaction can provide a useful biological model for designing social robots. Dogs can provide a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The dog has already been successfully applied as the prototype of non-human companions in humanrobot interaction research (Ichikawa et al, 2012;Koay et al, 2013;Kovács, Vincze, Gácsi, Miklósi, & Korondi, 2009;Lakatos, Gácsi, et al, 2014;Syrdal, Koay, Gácsi, Walters, & Dautenhahn, 2010). Social robots are designed to actively interact with humans and, similarly to dogs, they need to fulfil double criteria: i) successful performance of the actions necessary for their specific function (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The dog has already been successfully applied as the prototype of non-human companions in humanrobot interaction research (Ichikawa et al, 2012;Koay et al, 2013;Kovács, Vincze, Gácsi, Miklósi, & Korondi, 2009;Lakatos, Gácsi, et al, 2014;Syrdal, Koay, Gácsi, Walters, & Dautenhahn, 2010). Social robots are designed to actively interact with humans and, similarly to dogs, they need to fulfil double criteria: i) successful performance of the actions necessary for their specific function (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In order to test more directly if the stimuli used in the current experiment induced a cognitive conflict with regard to mind perception, we asked 55 participants (24 male; mean age= 36.8 years) in a post-hoc experiment to rate the stimuli regarding their ability of having a mind (i.e., using a Likert scale, following the procedure of Martini et al, 2016) and 161 participants (78 male; mean age= 33.8 years) in another post-hoc experiment to categorize the stimuli in a force-choice scenario into human and nonhuman (i.e., measuring percent of human versus non-human categorizations and reaction times, following the procedure of Lakatos, Gácsi, Konok, Brúder, Bereczky, Korondi, & Miklósi, 2014). Both experiments revealed that the humanoid stimulus was more difficult to classify than the other stimuli, as indicated by more ambiguous mind ratings, as well as less consensus and longer reaction times for the categorization of the humanoid stimulus compared to the other three stimuli; see Supplementary Materials (Section 1) for more details on the methods used and Figure 5 for a summary of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The robot identification is implemented to determine the dynamic model related to the inertia matrix, Coriolis, gravitational and friction torque effects are shown in (1). The robust predictive controllers are designed according to the robot dynamic model, characterized by each joint motion.…”
Section: Robot Control System Architecturementioning
confidence: 99%
“…The adaptive controllers allowed to generate robot motions with personalized interaction between human, environmental, and robot states. Experimental video of this work showing the expressive robot motion during the human and environmental interaction can be visualized in the link (1) .…”
Section: Variation Of Robot Temperaturementioning
confidence: 99%